Subcutaneous Buprenorphine Extended-Release Use Among Pregnant and Postpartum Women. Issue 2 (24th June 2021) - Cleary, E.M.; Byron, R.K.; Hinely, K.A.; Talley, A.W.; Costantine, M.M.; Rood, K.M.
Abstract : ( Obstet Gynecol . 2020;136:902–903) Sublingual buprenorphine is used to treat moderate-to-severe opioid-use disorder (OUD) in pregnant and lactating women. Its advantages over methadone are fewer cardiac arrhythmias, fewer death due to overdose, and less severe withdrawal symptoms from opioids in neonates. Extended-release buprenorphine has recently been approved by the U.S. Food and Drug Administration for OUD treatment in nonpregnant women, who have been stable on daily sublingual buprenorphine. However, data on its use in pregnant and lactating women is unknown since this population was not included in Phase 1 through Phase 3 trials. The aim of this study was to assess the use of extended-release buprenorphine for the treatment of OUD in pregnant and lactating women.